The Choice of Optimally Necessary Devices for Endovascular Treatment of Coarctation of the Aorta - Bogdan V. Cherpak; Nataliia S. Yaschuk; Yuliia V. Yermolovych; Oleksandr S. Golovenko; Yuriy V. Panichkin (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To determine the optimally necessary devices for endovascular stenting of coarctation of the aorta (CoA), considering the anatomical features of the defect and the age of the patient.Materials and methods. Examination and endovascular treatment of 189 patients aged 5 to 60 years with CoA of different anatomical and morphological variants was performed.Results and discussion. We presented the clinical features of different anatomical andmorphological variants of CoA. Endovascular treatment of CoA with stenting is considered the best method for adolescents and adults, due to the lower risk of aneurysm formation compared to balloon angioplasty. We were able to successfully reduce the invasive pressure gradient in patients of different ages and to establish dependence of the frequency of complications on the type of the stent used. There were no cases of in-hospital death. The effectiveness of the intervention was 99.4 %. All the patients were discharged from the hospital in good condition 3-7 days (3.3 ± 1.9 days) after the procedure. Currently, 95.7 % are being followed up. During the 5-year follow-up period, 1 patient died due to concomitant heart failure, heart rhythm disturbances (atrial fibrillation) and mitral insufficiency. There were 10.1 % patients (n = 19) with complications: 4.9 % (n = 4) with open-cell stents, 12.1 % (n = 13) with closed-cell stents, 2.2 % (n = 4) with stent-grafts, 7.9 % (n = 16) with uncovered stents. The frequency of reinterventions was 45.0 % in patients older than 25 years, 37.2 % in those aged 5-18 years and 17.6 % in those aged 19-25 years.Conclusions. The choice of optimally necessary devices for endovascular stenting of the aorta is recommended to be carried out considering the anatomical features of the defect and the age of the patient.